The Art of Digital Curation: Co-operative Stewardship of Net-Based Art - Post, Colin (Archivaria, 2021)
Artists have long engaged with digital and networked technologies in critical and creative ways to explore both new art forms and novel ways of disseminating artworks. Net-based artworks are often created with the intent to circulate outside traditional institutional spaces, and many are shared via artist-run platforms that involve curatorial practices distinct from those of museums or commercial galleries. This article focuses on a particular artist-run platform called Paper-Thin, characterizing the activities involved in managing the platform as digital curation in a polysemous sense – as both the curation of digital artworks and the stewardship of digital information in a complex technological ecosystem. While scholars and cultural heritage professionals have developed innovative preservation strategies for digital and new media artworks housed in institutional collections, the ongoing care of artworks shared through networked alternative spaces is largely carried out co-operatively by the artists and curators of these platforms. Drawing on Howard Becker’s sociological theory of art worlds as networks of co-operative actors, this article describes the patterns of co-operative work involved in creating, exhibiting, and then caring for Net-based art. The article outlines the importance, for cultural heritage professionals, of understanding the digital-curation practices of artists, as these artist-run networked platforms demonstrate emergent approaches to the stewardship of digital culture that move beyond a custodial paradigm.